The Iron Age in Northern Britain : Britons and Romans, Natives and Settlers - Harding, D. W. (Taylor and Francis, 2017)
Cover -- Title -- Copyright -- CONTENTS -- List of figures -- List of colour plates -- Preface -- PART I The legacy of the past -- 1 Introduction: the archaeological framework -- PART II The earlier Iron Age -- 2 Brigantia and northern England -- 3 The Borders and southern Scotland -- 4 Central and eastern Scotland -- 5 Argyll and Atlantic Scotland -- PART III The Roman Iron Age and its impact -- 6 Romanization to the northern frontier -- 7 Romanization between and beyond the frontiers -- PART IV The later Iron Age -- 8 The Borders and southern Scotland -- 9 Central and eastern Scotland -- 10 Argyll and Atlantic Scotland -- PART V Review and conclusion -- 11 Settlement and society: continuity and change -- Abbreviations -- Bibliography -- Index.